Survival prediction among pathologic T4 bladder cancer patients following cytoreductive cystectomy: A retrospective single-center study - Bai, Xuesong; Chen, Guo; Shang, Shihai; Li, Senlin; Liu, Huanrui; Feng, Zhenwei; Gou, Xin (Frontiers in Surgery, 2023)
Objectives This retrospective study aimed to describe our institutional experience with cytoreductive cystectomy (Cx) in patients with pathological T4 (pT4) bladder cancer (BCa) and to investigate the clinicopathologic factors that can predict patient survival outcomes. Methods We reviewed the baseline demographics, clinicopathologic features, perioperative complications, and follow-up data of 44 patients who underwent Cx for pT4 BCa at our institution between 2013 and 2021. The Kaplan–Meier curve and the log-rank test were used to analyze progression-free survival (PFS) and overall survival (OS). Univariate and multivariate analyses were performed using the Cox regression model. Results The median age of the patients was 68 years [95% confidence interval (CI) 49–81]. Overall, 21 patients (47.7%) were estimated to have a high age-adjusted Charlson comorbidity index (ACCI) score (>4), and nine patients (20.5%) had pT4b substage BCa. None of the patients died of complications within 30–90 days after surgery. Severe complications occurred in 16% (n = 7) of patients within 30–90 days. During a median follow-up of 51 months, disease progression was detected in 25 patients (56.8%), and 29 patients (65.9%) died of any cause. The median PFS and OS were 15.0 and 21.0 months, respectively. The Kaplan–Meier analysis indicated that patients with high ACCI scores or pT4b BCa had worse PFS (P = 0.003 and P = 0.002, respectively) and OS (P = 0.016 and P = 0.034, respectively) than those with low ACCI scores or pT4a BCa. On multivariate analysis, pT4b substage [hazard ratio (HR), 4.166; 95% CI, 1.549–11.206; P = 0.005] and ACCI score >4 (HR, 2.329; 95% CI, 1.105–4.908; P = 0.026) remained independent risk factors for PFS and OS, respectively. Conclusion Our study revealed that the pT4b substage is associated with a poor prognosis and that the ACCI score is a relevant and practical method to evaluate survival outcomes in patients with pT4 BCa after Cx.